Implementasi Metode Fonik dalam Pengenalan Bunyi Bahasa Inggris - Prayogo, Agus; Widyaningrum, Lulut (LP2M of Institute for Research and Community Services - UIN Walisongo, 2017)
Each language has a different sound system and syllable structure with varied complexity. English is a language that has complicated spellings and syllables, so it is necessary to learn the pronunciation of English words in terms of phonemes and alphabets. The difficulty for non-native English speakers is the very small vocal movement, except in a careful pronunciation. This article aims at describing the teacher empowerment program with three main designs begins with socialization, training, and guidance to teachers. The main objective of this program is to introduce ways that can be done by English teachers at schools and madrasas in the Sub-Region of Boja, Kendal regency, Central Java, in applying phonics-based teaching method and providing guidance to the teachers during the implementation process.